(untitled) (Web of Technology: Multidimensional Research Journal, 2026)
The article discusses the issues related to potential of gamification for teaching military specialties. The specificity of military education differentiates it from other professions; therefore, teaching methods should be adapted. Having analyzed the main problems in implementation of gamification in military higher education through scaffolded progression systems, philosophy of iterative failure, social and collaborative layers, four activities were developed. Practical results demonstrated that motivation to learn and overall quality of developed skills were sufficiently improved within such activities.